Visual Grammar and Aesthetic Differentiation of Geometric, Organic and Hybrid Zentangle Motifs - Ersa Aliyya; Achmad Haldani Destiarmand (International Journal of Multidisciplinary Research of Higher Education, 2026)
Research on Zentangle has largely emphasized psychological, therapeutic, and educational outcomes, while the motifs themselves remain underexplored as visual and aesthetic systems. This study addresses that gap by systematically examining the visual grammar and aesthetic differentiation of geometric, organic, and hybrid Zentangle motifs. The objective is to construct a comparative framework that clarifies how different motif categories generate distinct visual and aesthetic impressions. A qualitative descriptive–analytical design was applied to thirty purposively selected motifs. Data collection involved visual observation, literature review, and documentation. Analysis proceeded in two stages: first, visual elements and organizational relations were mapped using Wucius Wong’s framework; second, aesthetic interpretation was conducted through Anak Agung Made Djelantik’s triadic aspects of form, content, and presentation. Form encompassed the structural composition of lines, shapes, and spatial organization; content referred to expressive meaning conveyed through rhythm, balance, and symbolic resonance; presentation highlighted sensory impact, including clarity, harmony, and dynamic appeal. Results revealed that lines and repetition consistently functioned as principal devices across categories. Geometric motifs emphasized straight lines, angular fields, and formal structures; organic motifs emphasized curved lines, rounded fields, and flowing arrangements; hybrid motifs integrated structural regularity with organic flexibility. The study contributes a systematic comparative model for reading nonrepresentational pattern-based visuals and offers implications for motif development in surface design, textiles, illustration, and digital art.